2011
DOI: 10.1016/j.powtec.2010.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Borosilicate and aluminosilicate pollucite nanocrystals for the storage of radionuclides

Abstract: Cesium can be encapsulated in crystalline aluminosilicates or borosilicates of ANA framework type by hydrothermal synthesis from alkaline solutions at a temperature as low as 115°C. No miscibility gap is observed in the borosilicate-aluminosilicate solid solution. The presence of cesium in the synthesis batch slightly decreases the yield of incorporation of boron in the silicate framework. Nanocrystals from 25 to 50 nm are formed in most of the synthesis conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…These findings suggest that the compressibility of MFI porous materials increases with increasing their hydrophobic character, that is their Si/Al ratio (20.4 and 11.4 for Na-ZSM-5 and H-ZSM-5, respectively). This conclusion is confirmed by the preliminary data obtained on two silicalite samples and on natural mutinaite, characterized by different Si/Al ratio and water content [17,18].…”
Section: P (Gpa)supporting
confidence: 74%
See 2 more Smart Citations
“…These findings suggest that the compressibility of MFI porous materials increases with increasing their hydrophobic character, that is their Si/Al ratio (20.4 and 11.4 for Na-ZSM-5 and H-ZSM-5, respectively). This conclusion is confirmed by the preliminary data obtained on two silicalite samples and on natural mutinaite, characterized by different Si/Al ratio and water content [17,18].…”
Section: P (Gpa)supporting
confidence: 74%
“…For these reasons, as part of a wider project aimed to the study of the elastic behavior of microporous materials [7][8][9][10][11][12][13][14][15], we have performed in-situ synchrotron X-ray powder diffraction (XRPD) experiments on MFI-type zeolites with different framework Si/Al ratio and different extraframework content -namely Na-ZSM-5 [16], H-ZSM-5, and silicalite and mutinaite [17,18] -using (16:3:1) methanol:ethanol:water (m.e.w.) and/or silicone oil (s.o.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, analcime is fairly well able to incorporate Cs into its framework during crystallization above 200°C (Barrer 1978). Recently, Montagna et al (2010) demonstrated that Cs can be entrapped in analcime framework-type alumosilicates by hydrothermal synthesis at 115°C. Incorporation into the solid solutions between analcime and pollucite is suggested to be the major mechanism for cesium retention at 120°C, as suggested by Inagaki et al (2006).…”
Section: Co Sr and Cs Sorption Properties Of The Analcime-containingmentioning
confidence: 99%
“…Pollucite (CsAlSi 2 O 6 ), belonging to the zeolite family of analcime [13,14], is considered as a perfect mineral for immobilization of Cs due to its low leaching rate and good thermal stability [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%